2011
DOI: 10.1016/j.jmgm.2011.03.004
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular modelling and competition binding study of Br-noscapine and colchicine provide insight into noscapinoid–tubulin binding site

Abstract: We have previously discovered the tubulin-binding anti-cancer properties of noscapine and its derivatives (noscapinoids). Here, we present three lines of evidence that noscapinoids bind at or near the well studied colchicine binding site of tubulin: 1) In silico molecular docking studies of Br-noscapine and noscapine yield highest docking score with the well characterised colchicine-binding site from the co-crystal structure; 2) the molecular mechanics-generalized Born/surface area (MM-GB/SA) scoring results Δ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 47 publications
0
49
0
Order By: Relevance
“…Thus, minimization and then optimization of ligands using OPLS_2005 force field were performed to get one final 3D representative model of all ligands ready to dock. (Naik et al, 2011). For the preparation of protein molecules the crystal structures of protein were imported to the protein preparation wizard application of maestro 9.6 (Naik et al, 2011).…”
Section: Ligand and Protein Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, minimization and then optimization of ligands using OPLS_2005 force field were performed to get one final 3D representative model of all ligands ready to dock. (Naik et al, 2011). For the preparation of protein molecules the crystal structures of protein were imported to the protein preparation wizard application of maestro 9.6 (Naik et al, 2011).…”
Section: Ligand and Protein Preparationmentioning
confidence: 99%
“…(Naik et al, 2011). For the preparation of protein molecules the crystal structures of protein were imported to the protein preparation wizard application of maestro 9.6 (Naik et al, 2011). The various step involved in protein preparation steps include preprocess, review, modiefy and refinement.…”
Section: Ligand and Protein Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, only one piece of experimental evidence (competition interaction of Br-noscapine with colchicine binding) is so far reported that revealed a binding site of noscapinoid at or near the colchicine binding site of tubulin [21]. We reported that Br-noscapine produced a competition of 66% with colchicine at a concentration of 100 lM.…”
Section: Computational Studymentioning
confidence: 83%
“…Computational docking and competition studies of its derivative, 9-bromo-noscapine, point to binding with tubulin at a site overlapping with colchicine binding site [21]. The binding site is located at the interface between a-and b-tubulin and is large in volume (1,109.95 Å 3 ).…”
Section: Introductionmentioning
confidence: 99%